2017
DOI: 10.3390/ijerph14010068
|View full text |Cite
|
Sign up to set email alerts
|

New Immunotherapy Strategies in Breast Cancer

Abstract: Breast cancer is the most commonly diagnosed cancer among women. Therapeutic treatments for breast cancer generally include surgery, chemotherapy, radiotherapy, endocrinotherapy and molecular targeted therapy. With the development of molecular biology, immunology and pharmacogenomics, immunotherapy becomes a promising new field in breast cancer therapies. In this review, we discussed recent progress in breast cancer immunotherapy, including cancer vaccines, bispecific antibodies, and immune checkpoint inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 92 publications
(94 reference statements)
2
71
0
1
Order By: Relevance
“…Recently, many studies have found that inflammation and immunity play critical roles in tumor initiation, invasion, and metastasis [16]. Host anti-tumor immunity might offer a new strategy for curing BC [18,26,32]. The basic immune surveillance of the body and changes in systemic immune status, affect responses to therapy and even prognosis of BC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have found that inflammation and immunity play critical roles in tumor initiation, invasion, and metastasis [16]. Host anti-tumor immunity might offer a new strategy for curing BC [18,26,32]. The basic immune surveillance of the body and changes in systemic immune status, affect responses to therapy and even prognosis of BC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the newer targeted agents or modalities exhibit a similar frequency and severity of toxicities as traditional cytotoxic agents do, albeit with differences in preference for the organs/tissues that are involved . Many unanticipated short‐ and long‐term adverse effects on multiple organs/tissues have shown the limitations of the new therapies, although MTTs have improved the overall survival of cancer patients over the past two decades, and advanced immunotherapies are promising to improve the outcomes of certain types of cancers (ICIs and CART). Cardiac complications associated with cancer treatment represent unresolved and potentially life‐threatening conditions in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Deaths occur despite conventional treatments and innovative techniques in surgery, chemotherapy and radiotherapy (Palathinkal et al, 2014). Attempting to reduce the death rate, new treatment modalities with low side effects and maximum efficacy are being investigated (Yu et al, 2017). One such treatment modality is immunotherapy, which is based on stimulating or priming the patient's immune system to attack malignant tumors.…”
Section: Introductionmentioning
confidence: 99%